Increase in self-reported migraine prevalence in the Danish adult population: a prospective longitudinal population-based study. Issue 4 (2nd July 2012) - Le, Han; Tfelt-Hansen, Peer; Skytthe, Axel; Kyvik, Kirsten Ohm; Olesen, Jes
Abstract : Objective: It is uncertain whether migraine prevalence has increased in modern society. The aim of this study was to assess any change in migraine prevalence over an 8-year period among the adult population in Denmark. Design: Prospective longitudinal population-based study. Setting: 30 000 twin individuals were invited to participate in two cross-sectional questionnaire surveys containing validated questions to diagnose migraine in 1994 and 2002. The twins are representative of the Danish population with regard to migraine and other somatic diseases. Participants: The 1994 cohort comprised 28 571 twin individuals aged 12–41 years and the 2002 cohort 31 865 twin individuals aged 20–71 years. Outcome measures: Sex-, age- and subtype-specific incidence and lifetime prevalence as well as 1-year prevalence of migraine. Results: 1-year prevalence in 2002 was 12.3% for migraine, 4.1% for migraine with aura and 8.2% for migraine without aura. Lifetime prevalence of migraine was 16.1% in 1994 (aged 12–41 years) and 25.2% in 2002 (aged 20–71 years). Lifetime prevalence of migraine for age 20–41 was increased from 1994 to 2002 (18.5% vs 24.5%) by 32.2% (95% CI 27.0% to 37.3%; p<0.001). The difference was primarily seen in the population older than 32 years. The increase was especially evident in migraine with aura (5.6% vs 9.4%, p<0.001) but also a significant increase in migraine without aura was found (13.0% vs 15.1%, p<0.001). Eight-year period incidence rate of migraine was 0.141 corresponding to an average annual incidence rate of 17.6 per 1000 person-years. Conclusions: Lifetime prevalence of migraine in Denmark increased substantially from 1994 to 2002. Part of the increase may be due to increased medical consultation resulting in increased rate of physician diagnosis or awareness due to previously participation in the 1994 survey. It is pertinent to study the environmental causes of the increase and to implement preventive measures.